Editorial: Optimisation methods of road pricing - Zhang, Xiaoning (European Journal of Transport and Infrastructure Research, 2014)
Toll charges are classified into congestion tolls (congestion pricing) and road tolls (private pricing) respectively, according to the purpose of pricing. Congestion pricing is used to mitigate network congestion by shifting traffic flow from peak periods to off-peak periods, from congested routes to less congested routes, or from private cars to public transport. Private toll pricing is used to recoup construction or maintenance costs of road links, when they are built fully or partially on private investment. This special issue reports some recent developments in road pricing. Three papers investigate congestion pricing, and one paper deals with toll adjustment for road franchising. The optimisation models and theoretical findings might be useful and meaningful for future research on road pricing.